Effects of supplemental source of magnesium and inclusion of buffer on ruminal microbial fermentation in continuous culture - Arce Cordero, José Alberto (2021)
José Alberto Arce Cordero realizó esta publicación durante un programa de doctorado patrocinado por la Universidad de Costa Rica